Nutritional and health benefits of papaya: a review - S B, Nagarathna; Jain, S K; Champawat, P S; Mogra, Renu; Maherchandani, J K (Journal of Postharvest Technology, 2021)
The papaya (Carica papaya Linn) is a fruit-bearing plant that grows in tropical and subtropical regions and belongs to the Caricaceae family. It is mainly known for food and nutritional values throughout the world. The different parts of papaya plant such as leaves, seeds, stem, bark, roots, latex and fruit are economically more important because they possess excellent nutritional as well as medicinal properties. Leaves are used as a food, medicine and industrial applications. Compared to pulp and seeds, leaves are rich in major nutrients such as proteins, carbohydrates, fiber are small amount of fat. It contains micronutrients such as potassium, magnesium, iron, calcium, zinc, chromium, phosphorous, manganese. Vitamins such as thiamine, riboflavin, niacin, C, and E. Leaves are also good source of phytochemicals which have the ability to prevent diseases such as alkaloid, glycoside, flavonoid, phenol, polyphenol, saponin, tannin, and steroid. Also with good source of carotenoids they possess medicinal properties like antiseptic, anti-inflammatory, antifertility, abortifacient, hepatoprotective, wound healing and antitumor. The nutrient and phytochemicals present in eaves helps to increase appetite, improves digestion, reduce inflammation, supports the functioning of cardiovascular diseases, normalizes blood pressure and digestive system and also helps to increase white blood cells and platelets.